Internet Media Exposure to Premarital Sexual Behavior in Students at SMAN 1 Dringu, Probolinggo Regency 2023 - Kusumawardani, Nurbaity; Ramani, Andrei; Wicaksono, Dimas Bagus Cahyaningrat (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Premarital sexual behavior carries the risk of experiencing unwanted pregnancy and acquiring sexually transmitted infections (STIs). Various factors, including internal factors such as individual characteristics and low knowledge of reproductive health and external factors such as exposure to internet media, influence premarital sexual behavior. Aims: The research aims to determine the relationship between internet media exposure and premarital sexual behavior among students at SMAN 1 Dringu, Probolinggo Regency, in 2023. Method: The research uses primary data, with 93 respondents as sample size. The sampling technique uses a proportional stratified random sampling technique. Results: The research results showed that 67.7% of respondents had engaged in premarital sexual behavior. Conclusion: Regarding the gender factor, knowledge of adolescent reproductive health, duration of internet use, access to entertainment content, and access to pornographic content have significant relationships with premarital sexual behavior. The type of access device, frequency of internet use, educational content, communication content, and buying and selling content in internet media use have no relationship with premarital sexual behavior.